Perbedaan Kelelahan Perawat Ruang Rawat Inap 2 Shift/hari dengan 3 Shift/hari di RS Baladhika Husada dan RSD Kalisat Kabupaten jember (The Differences of Burnout of The Nurses in Inpatient’s Room with 2 Shift/Day and 3 Shift/Day in Baladhika Husada Hospit - Ria Aridya Liarucha; Dodi Wijaya; Hanny Rasni (UPT Percetakan dan Penerbitan Universitas Jember, 2016)
Burnout was combination of the physical, psychological, and emotional exhaustion. The differences of job schedules arrangement make each nurses has different duration when giving services. The differences had various effects on their condition of burnout. The goal of this study was analyzed the various burnout of nurses in inpatient room with 2 shift/day and 3 shift/day in Baladhika Husada Hospital and Kalisat Regional Hospital in Jember Regency. The differences of job schedule arrangement causes the duration of nurses’ shift were different. The differences of the duration could leads various burnout happens to nurses. This study was non experimental study with cross sectional study design. Researchers used comparative analysis to compare two groups of independent variables.This study used 60 samples of nurse which used consecutive sampling. The results of Mann Whitney showed p value = 0,683 (p value > α) so, it concluded that there was no differences in burnout of nurses in inpatients’ room with 2 shift/day and 3 shift/day in Baladika Husada hospital and Kalisat regional hospital Jember Regency. It could be influenced by many factors. The factors were workload, competence culture, and motivation. This research recommended the hospital attempted to reduce or minimize burnout by applied good managerial system. Keywords : burnout, work shift, nurses